2012
DOI: 10.1007/s12224-012-9139-8
|View full text |Cite
|
Sign up to set email alerts
|

Classifying and Mapping Potential Distribution of Forest Types Using a Finite Mixture Model

Abstract: The present paper presents the application of a finite mixture model (FMM) to analyze spatially explicit data on forest composition and environmental variables to produce a high-resolution map of their current potential distribution. FMM provides a convenient yet formal setting for model-based clustering. Within this framework, forest data are assumed to come from an underlying FMM, where each mixture component corresponds to a cluster and each cluster is characterized by a different composition of tree specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Although Q. robur extends to high latitudes (up to 60° N -Repo et al 2008), it is often limited by short vegetative periods and cold damage (Jensen 2000). Our findings are consistent with those of Attorre et al (2012) who reported that the presence of Q. robur was correlated with the warm temperatures occurring in temperate areas of Italy, which suggests a preference of the species for relatively low altitudes. In our study, this results in a geographical disjunction between Q. petraea (restricted to cold sites) and Q. robur (dominating warm areas at low and medium altitude).…”
Section: Discussionsupporting
confidence: 90%
“…Although Q. robur extends to high latitudes (up to 60° N -Repo et al 2008), it is often limited by short vegetative periods and cold damage (Jensen 2000). Our findings are consistent with those of Attorre et al (2012) who reported that the presence of Q. robur was correlated with the warm temperatures occurring in temperate areas of Italy, which suggests a preference of the species for relatively low altitudes. In our study, this results in a geographical disjunction between Q. petraea (restricted to cold sites) and Q. robur (dominating warm areas at low and medium altitude).…”
Section: Discussionsupporting
confidence: 90%
“…), or rules for choosing one type as “present” from probabilistic predictions (Hemsing & Bryn ; Attorre et al. ; Reger et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of initial model probabilities is not fully justified and has been avoided in more recent studies (Hemsing & Bryn ; Attorre et al. ; Reger et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations